James Meade. - Vines, D; Weale, M (Macmillan Publishers, 2009)
This article explains the part that Meade played in the creation of Keynes's General Theory, describes his work with Keynes during the Second World War in the creation of the IMF and the GATT, and summarizes the ideas in The Theory of International Economic Policy for which Meade was awarded the Nobel Prize in 1977. It also sets out the role that Meade played in the construction of the inflation-targeting regime which became the centrepiece of British macroeconomic policymaking in the 1990s.